Quizzz Application As A Learning Media Children Aged 5-6 Years at TK Islam Alazhar 1 Kebayoran Baru Jakarta Selatan - Babay Nurbani; Ana Mariana; Hulailah Istiqlaliyah (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2022)
This research is based on the use of Quizizz learning media in online learning. This study aims to find out how to analyze Quizizz learning media in online learning for Al Azhar Islamic Kindergarten 1 students, especially in group B3 with a total of 17 people. Data collection techniques using observation and documentation techniques. The results of the study on analyzing the Quizizz learning media in online learning at Al Azhar Islamic Kindergarten 1 showed that using the Quizizz application could foster students' motivation and interest in learning. This is because learning activities become fun